Pesantren readiness for the English programs - Mawardi Muhammad Nur; Sofyan Abdul Gani; Iskandar Abdul Samad; Wardani Muhammad Nur (Universitas Syiah Kuala, 2021)
Indonesia does not guarantee legitimately English as a second language. However, numerous Indonesian schools officially teach English, including pesantren (Mawardi, Maulidiansyah, Kamal, Nasai, 2019). Historically, the pesantren is an Islamic educational institution that teaches students through classical Islamic books (Fadhilah, 2011). Now, pesantren has been teaching modern lessons, including foreign languages such as English (Tahir, 2015). This study was designed to investigate the pesantren's readiness for English programs. Data collection was done by interview, observation, and documentation. Participants are people who are closely related to the object of research. A total of two English language coordinators were interviewed to obtain data on the pesantren's readiness for the English programs. The researchers also did observation and documentation to obtain supporting data from the research objects. The findings reveal that the pesantren's readiness for English language programs is outstanding in terms of the kinds of English programs, teachers' contributions, supporting facilities, and the pesantren environment itself. These findings are in line with previous researchers' findings, such as Insan (2019), Yulistiya (2020), and Setiawati (2018), stating that there are excellent programs for the advancement of students a foreign language.